(untitled) - Hutt, Michael D. (Orlando, Florida, 1998)
The book presents a clear, timely, and intersting examination of business marketing management. It provides an overview, highlights key concepts, and includes several carefully chosen examples of contemporary business marketing practice as well as a cogent summary and a set of provocative discussion questions
Keywords: Business,Marketing; Management,Management